2017
DOI: 10.5194/angeo-35-1269-2017
|View full text |Cite
|
Sign up to set email alerts
|

Tail reconnection in the global magnetospheric context: Vlasiator first results

Abstract: Abstract. The key dynamics of the magnetotail have been researched for decades and have been associated with either three-dimensional (3-D) plasma instabilities and/or magnetic reconnection. We apply a global hybrid-Vlasov code, Vlasiator, to simulate reconnection self-consistently in the ion kinetic scales in the noon-midnight meridional plane, including both dayside and nightside reconnection regions within the same simulation box. Our simulation represents a numerical experiment, which turns off the 3-D ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 24 publications
(32 reference statements)
3
55
0
Order By: Relevance
“…Although being computationally heavy, the hybrid‐Vlasov description has the advantage of providing noiseless ion VDFs. A number of studies utilizing this model have been already published and have shown a good agreement with previous numerical and observational works (Hoilijoki et al, , ; Kempf et al, ; Palmroth et al, , ; Pfau‐Kempf et al, ).…”
Section: Introductionsupporting
confidence: 83%
“…Although being computationally heavy, the hybrid‐Vlasov description has the advantage of providing noiseless ion VDFs. A number of studies utilizing this model have been already published and have shown a good agreement with previous numerical and observational works (Hoilijoki et al, , ; Kempf et al, ; Palmroth et al, , ; Pfau‐Kempf et al, ).…”
Section: Introductionsupporting
confidence: 83%
“…As a net effect, the flows are accelerated until ap-proximately −14 R E , after which they are decelerated (Karlsson et al, 2015). Fast flows that reach the transition region between the tail-like and dipolar magnetic field are diverted dawnward and duskward and can rebound from the strong dipole field (Birn et al, 1999;Chen and Wolf, 1999;Ohtani et al, 2009;Panov et al, 2010;Birn et al, 2011;McPherron et al, 2011;Juusola et al, 2013;Nakamura et al, 2013).…”
Section: Occurrence Of Plasma Sheet Flowsmentioning
confidence: 99%
“…Statistical results have demonstrated that the occurrence rate of flapping motions is similar to that of BBFs, and peak in the central part of the magnetotail (Sergeev et al, 2006). Empirical models (Petrukovich et al, 2008;Rong et al, 2010) have been constructed to describe the characteristics of flapping current sheets.…”
Section: Introductionmentioning
confidence: 99%